Varieties of populism and the challenges to Global Constitutionalism: Dangers promises and implications - Cédric M. Koch (Global Constitutionalism, 2021)
This article analyses the rise of populism and its discursive challenge to global constitutionalism (GC). It shows that populist contestation is more ambivalent than often suggested: its challenge depends on the populist variety and can both undermine or support liberal principles of GC. Building on the ideational approach to populism and a framework of transnational politicisation, a proposed typology identifies both 'communitarian types of populism' and 'cosmopolitan types of populism'. Illustrative case studies of the Alternative for Germany, the Polish Law and Justice Party, the Democracy in Europe Movement and Peru's Alberto Fujimori substantiate these empirically. While all cases contest a perceived lack of popular sovereignty in a largely non-majoritarian global constitutional order, varieties of populism present contrasting responses: communitarian types push for global de-constitutionalisation in line with illiberal nationalist majoritarianism, while cosmopolitan types support global constitutionalisation according to liberal and democratic principles. Further, neo-socialist populists campaign against neoliberal principles in GC, but remain divided about supporting political principles beyond the state. These findings suggest an emerging politicisation of the process of global constitutionalisation at the societal level according to principles of democratic legitimacy; and global constitutional differentiation depending on outcomes of these normatively ambivalent and empirically contingent political contests.
Keywords: 330; populism; global constitutionalism; liberalism; popular sovereignty; cosmopolitanism